(untitled) (Dandao Xuebao/Journal of Ballistics, 2023)
An overlapped foldable wing components with large aspect ratio were studied. The aerodynamic configuration of the wing components applied in the miniaturized gliding guided aerial ammunition was anayzed by numerical simulation and wind tunnel test,and the configuration parameters of the wing components were optimized. The aerodynamic characteristics and gliding performance of the wing components were verified by 3-DOF trajectory simulation. The results show that the aerodynamic layout of overlapped foldable wing components can greatly reduce the shape size of folded wing under the closed state. Under the restriction of the same structure and size envelope,the chord length of the wing can be twice as long as that of the symmetrica flat wing,and the area of lift surface can be effectively increased,and the high lift-drag ratio aerodynamic-configuration under size limitation was obtained. The structure of the wing components is simple and compact. The problems of structural efficiency and limited aerodynamic gain can be solved when the traditional folded wing is applied to miniaturized guided munition.